TEACHING THAT TRASCENDS THE CLASS ENVIRONMENT. TEACHERS’ VIEWS ABOUT THEIR ACTIVITIES AT SECONDARY SCHOOL - María Gloria Saucedo; María Teresa Alcalá; Horacio Ademar Ferreyra (Revista del Instituto de Investigaciones en Educación, 2019)
The progress of a research scholarship project is presented in this article. Teaching is approached from the perspectives of secondary school teachers. The main aim is to describe activities teachers do within the school organization and also the positions they build and also the relations they establish concerning the tasks they perform, the responsibilities and the roles they take beyond the classroom. We used an explorative – descriptive qualitative approach with case study as the methodological strategy. The data collection procedures are: semi structured interviews (with teachers of different subjects belonging to the departments of a secondary school as participants) and documentary analysis methodologically triangled. The results show that everyday teaching practice goes beyond the class environment since it involves an intertwined net of activities and relations that exceeds, frames and conditions it. Other ways of performing the teacher´s task and “teachers´ views,” crossed by the institutional re- configuration due to the joining of new groups of students framed in the emerging school and social configurations, are built here. Educational assumptions about traditional school and the teachers´ own task, teaching, are questioned. “Teaching” comes up as central, though clearly overloaded with activities which require social containment work for individuals with the right to secondary level education and the participation of teachers together with members of the educational community in the school organization.